Política educacional e participação: a organização do ensino de Abaetetuba/PA - BARBOSA, Thayane Silva (2022)
In the democratic system, education presents many changes throughout the history and therefore participation is an essential effect for the organization. Thus, it becomes important to understand the organization of the educational system in the municipality of Abaetetuba/PA and foster debates on the decision-making process on participation in this operation. The references of qualitative research in education were used by understand that this type of investigation is the most used in research in the human sciences and social and as a study strategy we will deal with a documentary research. We aim to analyze how the relations of participation of the school community occur in management decision-making in the educational system and understand how the school community contributes to the ordering of the educational system in this municipality. THE From this incursion it was possible to perceive that the educational system in Abaetetuba is still walking at a slow pace with regard to educational policy, still that there is community participation in the elaboration of public policies the implementation effective is non-existent within the democratic management of the school analyzed for the research. We consider that the study is relevant for the evaluation of the organization of the municipal education system in Baixo Tocantins and thus foster new perspectives of educational policy for the general population.